Imaging Techniques as an Aid in the Early Detection of Cardiac Amyloidosis - Santarelli, M.F.; Scipioni, M.; Genovesi, D.; Giorgetti, A.; Marzullo, P.; Landini, L. (Current Pharmaceutical Design, 2021)
The idea that performing a proper succession of imaging tests and techniques allows an accurate and early diagnosis of cardiac amyloidosis, avoiding the need to perform the myocardial biopsy, is becoming increasingly popular. Furthermore, being imaging techniques non-invasive, it is possible to perform the follow-up of the pathology through repeated image acquisitions. In the present review, the various innovative imaging methodologies are presented, and it is discussed how they have been applied for early diagnosis of cardiac amyloidosis (CA), also to distinguish the two most frequent subtypes in CA: immunoglobulin light chain amyloidosis (AL) and transthyretin amyloidosis (ATTR); this allows to perform the therapy in a targeted and rapid manner.
Keywords: pathology